Magna Carta and Maintaining Human Rights: Principles and Effects - MEHDA, Yagouta; AMRI, Amina (University of Eloued جامعة الوادي, 2024)
The current study aims at investigating the principles of the Magna Carta and how it affected the human rights over the centuries. It also discusses the extent to which the Magna Carta’s limited to some human rights issues. The study used a qualitative approach, using descriptive, analytical, and historical approaches to comprehensively investigate the impact of Magna Carta on the maintenance of human rights, principles and its impacts. The research findings reveal that the profound impact on human rights influences pivotal historical events like the English Civil War and the American Revolution. Also, its principles of due process, limited government, and individual liberties continue to shape legal frameworks and political discourse globally. Also, the critical evaluation reveals Magna Carta's limitations, urging a nuanced understanding of its historical context and contemporary relevance in addressing ongoing human rights challenges. تهدف الدراسة الحالية إلى التعرف على مبادئ الماجنا كارتا وكيفية تأثيرها على حقوق الإنسان عبر القرون. ويناقش هذا البحث أيضًا مدى اقتصار الماجنا كارتا على بعض قضايا حقوق الإنسان. وقد استخدم هذا البحث منهجًا نوعيًا، وذلك باستخدام المنهج الوصفي والتحليلي والتاريخي للتحقيق بشكل شامل في تأثير الماجنا كارتا على صيانة حقوق الإنسان ومبادئها وعناصرها. التأثيرات. تكشف نتائج البحث أن التأثير العميق للماجنا كارتا على حقوق الإنسان يؤثر على الأحداث التاريخية المحورية مثل الحرب الأهلية الإنجليزية والثورة الأمريكية. كما أن مبادئ ماجنا كارتا الخاصة بالإجراءات القانونية الواجبة، والحكومة المحدودة، والحريات الفردية تستمر في تشكيل الأطر القانونية والخطاب السياسي على مستوى العالم. ويكشف التقييم النقدي أيضًا عن حدود الماجنا كارتا، ويحث على فهم دقيق لسياقها التاريخي وأهميتها المعاصرة في معالجة التحديات المستمرة في مجال حقوق الإنسان.
Keywords: الماجنا كارتا، حقوق الإنسان، الإجراءات القانونية الواجبة، الخطاب السياسي; Magna Carta; Human Rights; Due Process; Political Discourse